Analysis of the Planning Stage of the Natural and Social Sciences (IPAS) Instructional Design Based on Project-Based Learning - Yuliasari, Brigita; Atmojo, Idam Ragil Widianto; Matsuri, Matsuri; Suryandari, Kartika Chrysti (EduBasic Journal: Jurnal Pendidikan Dasar, 2025)
One of the learning models that involves three domains of learning outcomes (cognitive, affective, and psychomotor) is project-based learning in science subjects. In practice, the application of this model should also not contradict the prevailing curriculum (Merdeka Curriculum). This study aimed to analyse the planning of natural and social sciences (IPAS) instructional design based on the project-based learning (PjBL) model. This research is descriptive qualitative with a case study method. The research participants comprise a teacher, a school principal, and 18 students of the 5th grade. The data were collected through interviews, observations, and documentation. The data analysis technique used was Milles Huberman's interactive analysis. The researchers applied data validity test with triangulation of sources, techniques, and theories. The results of the study suggested that the planning of teaching modules based on the project-based learning model created by the teacher considered students’ learning achievements in line with the demands of the Merdeka Curriculum in terms of syntaxes of the project-based learning. The results imply that teachers need to design systematic project stages, provide adequate resources, and provide space for collaboration and student creativity, and a rubric for assessing students' processes and outcomes in the planning stage of the IPAS instructional design based on project-based learning consistently in the future.